Shifting the Paradigm: Monitoring Access in Medicare Managed Care - Docteur, Elizabeth R. (CENTERS for MEDICARE & MEDICAID SERVICES, 1996)
Medicare managed care enrollment growth points to the need to develop an approach for monitoring access to care for the increasing number of beneficiaries who use these arrangements. This article describes the issues to be addressed in designing a system for monitoring managed care plan enrollees' ability to obtain needed medical care on a timely basis. We review components of the monitoring approach used for traditional fee-for-service (FFS) Medicare, including the conceptual framework, data, measures, and subgroups targeted in monitoring efforts, and discuss the adaptation of that approach for monitoring access in Medicare managed care.